Google's keyword analysis tool and compare its various metrics for finding the most popular search terms on the web - Tusar, Md. Fazlul Karim (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.